AUDIT OF SURGICAL SITE INFECTION AT TYPE D HOSPITAL, TORU, MARDAN, KPK, PAKISTAN. - Asad Ali; Aiman Waheed; Muhammad Rashid Waheed; Mohsin Rasheed; Shafqat Wasim; Aiman Sattar Memon; Ehsan Ullah (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: SSIs occur at or near the surgical incision within 30 days of the procedure or within one year if an implant is placed.Objectives: The primary objective of the study is to find the surgical site infection and their risk factors at Type D hospital, Mardan, KPK, Pakistan.Methods: This clinical audit was done in Type D hospital, Toru Mardan KPK, Pakistan from January 2023 to January 2024. We retrospectively reviewed all the patients who underwent surgery at different departments of hospital. Total of 1000 patients were done with different surgeries in this hospital. Electronic Health Records (EHRs) are reviewed to obtain patient demographics, medical history, details of surgical procedures, and postoperative outcomes. Surgical logs provide information on the types and frequencies of surgeries performed.Results: Data were collected retrospectively from 1000 patients undergone surgeries at different departments. Mostly patients were registered in general surgery department which were 200 patients. The lowest rate of SSI was in Gynecological Surgery which is 3.3%.Emergency surgeries contain the rate of SSI 8% and elective surgeries 4.5%.Conclusion: Audit of surgical site infections (SSIs) has provided critical insights into the incidence, risk factors, and effectiveness of preventive measures within the hospital setting. The overall SSI rate of 5% is indicative of both successes and areas needing improvement in infection control practices.